GPCR profiling: from hits to leads and from genotype to phenotype. (November 2015) - Cvijic, Mary Ellen; Sum, Chi Shing; Alt, Andrew; Zhang, Litao
Abstract : GPCRs remain one of the most important classes of drug targets and, therefore, GPCR assay development and high-throughput GPCR ligand profiling continue to be major efforts in drug discovery. This article focuses on GPCR platform strategies from hits to leads with miniaturized complex pharmacology approaches. Three main areas of GPCR profiling are discussed including pharmacologically relevant hit identification, the pharmacology dossier applied to parallel structure activity and structure liability relationships and high-throughput mechanism studies from genotype to phenotype.